CARACTERIZAÇÃO FISIOGRÁFICA DE UMA BACIA AFLUENTE AO RIO COMANDAÍ - Dorneles, Bruna Taciane Rodrigues; Siveris, Daniela Mittmann; Reckziegel, Tatiana; Bilhalva, Wagner Danton De Bittencourt (Salão do Conhecimento, 2018)
Pesquisa de iniciação cientifica na graduação.